(untitled) (Research, Society and Development, 2022)
The increase in life expectancy of individuals living with HIV has contributed to the manifestation of comorbidities due to multiple factors, such as HIV infection, use of antiretroviral drugs and aging. The use of other drugs and polypharmacy can compromise adherence to antiretroviral treatment due to potential drug interactions and adverse reactions. A cohort study was conducted with individuals living with HIV who started antiretroviral therapy (ART) in three specialized HIV/AIDS care services in Belo Horizonte, to describe the use of non-antiretroviral drugs and polypharmacy among treatment-naïve individuals in the period 12 months after starting ART. Data were collected through interviews, clinical records and computerized systems with data on the dispensing of antiretrovirals and laboratory tests of viral load and TCD4+ lymphocyte count. A total of 433 individuals were included, of which 70.0% had a record of using non-antiretroviral drugs concomitantly with ART and 7.9% of polypharmacy within 12 months of treatment. The most used therapeutic subgroups were antibacterials for systemic use (29.6%), antihistamines for systemic use (7.1%), antimycobacterials (4.8%), antimycotics (4.8%) and psychoanaleptics (4, 4%). The most used drugs were sulfamethoxazole and trimethoprim (10.8%), benzathine benzylpenicillin (6.3%), loratadine (5.7%), azithromycin (4.8%) and fluconazole (4.7%). The use of non-antiretroviral drugs in the first 12 months of treatment was high, with an important share in polypharmacy. The most used drugs correspond to indications for prophylaxis and treatment of opportunistic infections and antiretroviral toxicities.